Generalized quantum rotation gates using STIRAP - Issoufa, Youssouf Hamidou; Az Eddine, Messikh; Wahiddin, Mohamed Ridza; Umarov, Bakhram A.; Gharib, Subhi Mahmoud Ahmed (2013)

(untitled)
In this paper we focus on the generalized quantum rotation gates in the presence of dephasing. We follow the model proposed by Lacour et. al. [1] and extend their technique by applying the quantum jump approach. This approach clearly illustrates the acquired phases which cannot be recompensated and leads to imperfect gates. Numerical solutions for these phases were obtained assuming realistic dephasing rates.